Multimodality Imaging in Secondary Mitral Regurgitation - Sharma, Harish; Liu, Boyang; Mahmoud-Elsayed, Hani; Myerson, Saul G.; Steeds, Richard P. (Frontiers in Cardiovascular Medicine, 2020)
Secondary mitral regurgitation (sMR) is characterized by left ventricular (LV) dilatation or dysfunction, resulting in failure of mitral leaflet coaptation. sMR complicates up to 35% of ischaemic cardiomyopathies (1) and 57% of dilated cardiomyopathies (2). Due to the prevalence of coronary artery disease worldwide, ischaemic cardiomyopathy is the most frequently encountered cause of sMR in clinical practice. Although mortality from cardiovascular disease has gradually fallen in Western countries, severe sMR remains an independent predictor of mortality (3) and hospitalization for heart failure (4). The presence of even mild sMR following acute MI reduces long-term survival free of major adverse events (1). Such adverse outcomes worsen as the severity of sMR increases, due to a cycle in which LV remodeling begets sMR and vice versa. Current guidelines do not recommend invasive treatment of the sMR alone as a first-line approach, due to the paucity of evidence supporting improvement in clinical outcomes. Furthermore, a lack of international consensus on the thresholds that define severe sMR has resulted in confusion amongst clinicians determining whether intervention is warranted (5, 6). The recent Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patients with Functional Mitral Regurgitation (COAPT) trial (7) assessing the effectiveness of transcatheter mitral valve repair is the first study to demonstrate mortality benefit from correction of sMR and has reignited interest in identifying patients who would benefit from mitral valve intervention. Multimodality imaging, including echocardiography and cardiovascular magnetic resonance (CMR), plays a key role in helping to diagnose, quantify, monitor, and risk stratify patients for surgical and transcatheter mitral valve interventions.